Implementasi Total Quality Management dalam Membangun Budaya Mutu Pendidikan di Era Revolusi Industri 4.0: Studi Kasus di SMP Islam Bunga Bangsa Samarinda - Argaricha, Amirah Sahda; Khojir, Khojir; Bahrani, Bahrani (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
This study aims to analyze the implementation of Total Quality Management (TQM) in building a culture of quality education during the Industrial Revolution 4.0 era at SMP Islam Bunga Bangsa Samarinda. In the context of global transformations demanding innovative and adaptive education systems, schools are required to deliver services that prioritize continuous improvement and stakeholder satisfaction. This research employed a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observations, and document analysis of the school's quality management policies and practices. The findings indicate that the implementation of TQM at SMP Islam Bunga Bangsa Samarinda includes strategic efforts such as improving the quality of teaching and administrative staff, optimizing academic and non-academic services, integrating technology into teaching and administration, and strengthening communication with parents. The success of TQM implementation is supported by visionary leadership, a sustainable performance evaluation system, and reward mechanisms that enhance staff motivation. The resulting quality culture has had a positive impact on student achievement, graduate competence, and overall parental satisfaction. Nonetheless, challenges include intergenerational differences among teachers, a lack of alignment between foundation policies and school operational strategies, and difficulties in maintaining teaching quality due to sudden staff turnover. The study concludes that TQM is effective in fostering a sustainable quality culture in the era of the industrial revolution, if it is supported by synergy across school components and responsive policy frameworks.